2019
DOI: 10.1016/j.jes.2019.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Uranium sequestration in sediment at an iron-rich contaminated site at Oak Ridge, Tennessee via. bioreduction followed by reoxidation

Abstract: This study evaluated uranium sequestration performance in iron-rich (30 g/kg) sediment via bioreduction followed by reoxidation. Field tests (1383 days) at Oak Ridge, Tennessee demonstrated that uranium contents in sediments increased after bioreduced sediments were re-exposed to nitrate and oxygen in contaminated groundwater. Bioreduction of contaminated sediments (1200 mg/kg U) with ethanol in microcosm reduced aqueous U from 0.37 to 0.023 mg/L. Aliquots of the bioreduced sediment were reoxidized with O2, H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
(112 reference statements)
0
3
0
1
Order By: Relevance
“…They are responsible for the bioremediation and immobilization of uranium when it enters the environment (soil, groundwater). Bioreduction, followed by reoxidation by oxygen, can sequestrate U via the formation of stable U-coated particles, as was shown by Li et al ( 2019 ). The dual effects of microorganisms on the behavior of uranium (reduction or rapid reoxidation), along with biosorption, bioaccumulation, and biomineralization, are reviewed in Cumberland et al ( 2016 ).…”
Section: Uraniummentioning
confidence: 68%
“…They are responsible for the bioremediation and immobilization of uranium when it enters the environment (soil, groundwater). Bioreduction, followed by reoxidation by oxygen, can sequestrate U via the formation of stable U-coated particles, as was shown by Li et al ( 2019 ). The dual effects of microorganisms on the behavior of uranium (reduction or rapid reoxidation), along with biosorption, bioaccumulation, and biomineralization, are reviewed in Cumberland et al ( 2016 ).…”
Section: Uraniummentioning
confidence: 68%
“…The extent of adsorption on Oak Ridge subsurface sediment increased sharply as the pH increased from 4.5 to 5.5, is at its maximum binding efficiency between pH 5.5 and 7.5, and then decreased sharply over the pH range of 7.5 to 8.5 as the concentration of dissolved carbonate and U(VI)-carbonate complexes increased ( (Barnett et al, 2002;Barnett et al, 2000). There has been an unusually large amount of research on U redox chemistry in Oak Ridge sediments, primarily because the DOE was interested in evaluating whether redox manipulations of the subsurface environment could be used to immobilize groundwater U (Kelly et al, 2010;Li et al, 2019a;Spain and Krumholz, 2011). Zhong et al (2005) showed that Oak ridge sediments could result in reductive precipitation of uranyl under natural conditions, but that the reduction was readily reversible.…”
Section: Discussion Of Potential Geochemical Processes Responsible Fo...mentioning
confidence: 99%
“…Zhong et al (2005) showed that Oak ridge sediments could result in reductive precipitation of uranyl under natural conditions, but that the reduction was readily reversible. Iron oxide coatings on Oak Ridge sediments were shown to play an important role in uranyl uptake (Li et al, 2019b;Stewart et al, 2010). Increases in groundwater calcium concentration further decreased uranyl sorption to an Oak Ridge Melton Branch Ridgetop sediment (Stewart et al, 2010).…”
Section: Discussion Of Potential Geochemical Processes Responsible Fo...mentioning
confidence: 99%
“…이차 Ca-U(Ⅵ)의 침전 또 는 탄산아연의 침전은 UO 2(s) 표면을 부동태화(passivation) 시켜 추가 산화를 방지하기 때문이다 (Cerrato et al, 2012). 최근 연구에 의하면 재산화된 우라늄을 격리하여 확산을 막을 수 있다 (Li et al, 2019). 이는 앞에서 밝혔듯이, U(Ⅳ) 와 반응하는 산화제가 Fe(Ⅱ) 등 다른 환원성 화합물과도 반응하여 결과적으로 생성된 Fe(Ⅲ) 산화물이 넓은 표면적 으로 U(Ⅵ)를 강하게 흡착하기 때문이다 (Estes and Powell, 2020).…”
Section: 미생물학적 환원unclassified